Synthesis of benzofuro- and benzothieno[2, 3-c]pyridines via copper-catalyzed [4 + 2] annulation of ketoxime acetates with acetoacetanilide. Issue 12 (8th April 2021) - Rong, Binsen; Xu, Gaochen; Yan, Huan; Zhang, Sai; Wu, Qinghuan; Zhu, Ning; Fang, Zheng; Duan, Jindian; Guo, Kai
Abstract : An efficient copper-catalyzed annulation of ketoxime acetates with acetoacetanilide has been developed for the facile synthesis of benzofuro- and benzothieno[2, 3- c ]pyridines. Abstract : An efficient copper-catalyzed annulation of ketoxime acetates with acetoacetanilide has been developed. This strategy provides an alternate route towards the synthesis of benzofuro- and benzothieno[2, 3- c ]pyridines with good functional group tolerance and operational simplicity. Mechanistic investigation indicates that an ionic pathway rather than a radical pathway was involved in the transformation.